Engineering Fourier planes for analog image processing - Muhammad 'Aqil Bin Rosdi (Nanyang Technological University, 2024)
This report delves into the realm of optical information processing, focusing on the implementation of edge detection within a Fourier domain-based 4f optical system. Utilising MATLAB and its Image Processing Toolbox, the project aims to design and optimise a system for real-time image processing. By initialising fundamental physical constants and system parameters, and employing Sobel operators within the Fourier domain, the study demonstrates effective edge detection of various input patterns, including structured geometric shapes and arbitrary images. The results underscore the potential of combining optical and computational techniques to achieve efficient and accurate edge detection.